A Qualitative Signature to Identify TERT Promoter Mutant High-Risk Tumors in Low-Grade Gliomas - Zheng, Weicheng; Zhang, Ruolan; Huang, Ziru; Li, Jianpeng; Wu, Haonan; Zhou, Yuwei; Zhu, Jinwei; Wang, Xianlong (Frontiers in Molecular Biosciences, 2022)
Background: Telomerase reverse transcriptase promoter (TERT-p) mutation has been frequently found in both low-grade gliomas (LGGs) and glioblastomas (GBMs), but it is associated with contrary prognosis. For the low-grade gliomas (Grades II-III), TERT-p mutant (mut) patients have a better prognosis than the wildtype (wt) patients, whereas for the GBMs (Grade IV), TERT-p mutation is related to a poor prognosis. We hypothesize that there exist high-risk patients in LGGs who share GBM-like molecular features, including TERT-p mutation, and need more intensive treatment than the other LGGs. A molecular signature is needed to identify these high-risk patients for an accurate and timely treatment. Methods: Using the within-sample relative gene expression orderings (REOs) of gene pairs, we identified the gene pairs with significantly stable REOs, respectively, in both the TERT-p mutant LGGs and GBMs but with opposite directions in the two groups. These reversely stable gene pairs were used as the molecular signature to stratify the LGGs into high-risk and low-risk groups. Results: A signature consisting of 21 gene pairs was developed, which can classify the TERT-p mutant LGGs into two groups with significantly different overall survival. The high-risk group has a similar genetic mutation profile and a similar survival profile as GBMs, and these high-risk tumors may progress to a more malignant state. Conclusions: The 21 gene-pair signature based on REOs is capable of identifying high-risk patients in LGGs and guiding the clinical choice for appropriate and timely intervention.